Next generation networks, mobility management and appliances in intelligent transport systems - Väärämäki, Tapio (2010)
For quite some time there has been discussion regarding convergence of networks. Access technologies of different characteristics are converging into one heterogeneous, but ubiquitous access network, where different access technologies with different parameters complement each other. To enable such a convergence, many challenges regarding network interworking must be solved. One of the major challenges is the mobility management across heterogeneous networks. This dissertation discusses mobility management in heterogeneous network environments. Mobility management is studied from the user point of view and a proposal of the mobility management system is suggested. The benefits of an introduced system are identified from both user and operator point of view. Currently, the major challenges for the introduced mobility management system are related to robust link information collecting. Thus integration with a standardized solution is researched. There are promising opportunities for such an implementation, but a strong consensus among the standardization organizations is required to achieve a common solution. The mobility management policies that define how the mobile node behaves between different networks are a part of this discussion. Intelligent Transport Systems are taken as an example of the environment where the multi-access networking provides significant advantages compared to single access connectivity. The benefits are discussed by both technology and business perspectives. The latter is supported by the techno-economic analysis that shows the strong potential of the solutions studied. The corresponding service and technology frameworks are researched and suggested as well.